Physical training in patients with chronic heart failure - A. V. Snytnikova; D. A. Andreev; A. A. Doletsky; A. V. Svet; A. V. Chaplygin (Кардиоваскулярная терапия и профилактика)
Chronic heart failure (CHF) manifests in heart insufficiency and inadequate blood flow in various organs and tissues. One of the most important CHF symptoms is reduced physical stress (PS) tolerability, due to impaired central hemodynamics and various peripheral mechanisms. Physical training (PT) improves PS tolerability, quality of life and prognosis in CHF patients. While PT effectiveness in CHF has been proved, there are various approaches to PT methodology. In particular, two types of PT are used – PT with constant PS intensity and interval PT. This literature review summarizes the evidence on the mechanisms of PS tolerability in CHF and PT effects in these patients. PT methodology (start time after decompensation, length, and intensity) is also discussed.